1991
DOI: 10.2466/pms.1991.72.2.411
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Imagery Scores

Abstract: Estimates of the stability of scores on imagery were given by 113 young adults, whose mean age was 16.6 yr., 129 middle adults, whose mean age was 29.9 yr., and 49 older adults, whose mean age was 53.3 yr. Significant correlations were obtained between scores given to 210 words by age and sex of groups, except for older women. Pearson correlations were calculated over words and not over subjects. The correlations were between scores of young people and adults .92, between young and old people .29, and between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…For example, on the 1-7 imageability scale, the following words easily evoke mental images according to one set of norms but not another: "norm" (2.5 in Cortese & Fugett, 2004;6.0 in Toglia & Battig, 1978), "head" (2.4 in Bird et al, 2001;6.8 in Cortese & Fugett, 2004) and "spire" (2.7 in Cortese & Fugett, 2004;5.5 in Scott et al, 2018). Indeed, previous work that has systematically examined the stability of imageability ratings has sometimes found major discrepancies between participant samples (e.g., Campos & Sueiro, 1991;Grandy et al, 2020). While newer imageability norms report consistency with existing ones in method and ratings (e.g., Bird et al 2001;Cortese & Schock, 2013;Scott et al, 2018), they nonetheless vary in terms of participants' age and country of testing, word samples and rating distributions, as well as testing methods (see Table 1 for an overview of the norms used in the current study).…”
Section: Weaker Than You Might Imagine: Imageability Effects On Word ...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, on the 1-7 imageability scale, the following words easily evoke mental images according to one set of norms but not another: "norm" (2.5 in Cortese & Fugett, 2004;6.0 in Toglia & Battig, 1978), "head" (2.4 in Bird et al, 2001;6.8 in Cortese & Fugett, 2004) and "spire" (2.7 in Cortese & Fugett, 2004;5.5 in Scott et al, 2018). Indeed, previous work that has systematically examined the stability of imageability ratings has sometimes found major discrepancies between participant samples (e.g., Campos & Sueiro, 1991;Grandy et al, 2020). While newer imageability norms report consistency with existing ones in method and ratings (e.g., Bird et al 2001;Cortese & Schock, 2013;Scott et al, 2018), they nonetheless vary in terms of participants' age and country of testing, word samples and rating distributions, as well as testing methods (see Table 1 for an overview of the norms used in the current study).…”
Section: Weaker Than You Might Imagine: Imageability Effects On Word ...mentioning
confidence: 99%
“…While newer imageability norms report consistency with existing ones in method and ratings (e.g., Bird et al 2001;Cortese & Schock, 2013;Scott et al, 2018), they nonetheless vary in terms of participants' age and country of testing, word samples and rating distributions, as well as testing methods (see Table 1 for an overview of the norms used in the current study). For instance, Campos & Sueiro (1991) correlated imageability ratings across age and sex, and found that while some subgroups rated imageability consistently (e.g., r = .94 for men vs. women aged 21-40), others did not (e.g., r = .14 for men vs. women aged 41-60; r = .33 for adults age 21-40 vs. 41-60). Clearly, whatever the reason for such discrepancies (e.g., age, sex, cultural change over time, geographic location), it is clear that different samples of participants sometimes base their imageability ratings on qualitatively different information, which in turn may influence the efficacy of those ratings in predicting word recognition performance.…”
Section: Weaker Than You Might Imagine: Imageability Effects On Word ...mentioning
confidence: 99%
“…While newer imageability norms report consistency with existing ones in method and ratings (e.g., Bird et al 2001;Cortese & Schock, 2013;Scott et al, 2018), they nonetheless vary in terms of participants' age and country of testing, word samples and rating distributions, as well as testing methods (see Table 1 for an overview of the norms used in the current study). For instance, Campos & Sueiro (1991) correlated imageability ratings across age and sex, and found that while some subgroups rated imageability consistently (e.g., r = .94 for men vs. women aged 21-40), others did not (e.g., r = .14 for men vs. women aged 41-60; r = .33…”
Section: Weaker Than You Might Imagine: Imageability Effects On Word ...mentioning
confidence: 99%